Provincial Economic Growth in Indonesia: Investigating with Inflation, Exchange Rates and Foreign Direct Investment - Sessu, Andi; Sjahruddin, Herman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
This study explores the determinants of Indonesia's economic growth factors through inflation, exchange rates and foreign direct investment based on a quantitative paradigm. This research uses all provinces in Indonesia as population except (Bengkulu, West Sulawesi, Maluku, Gorontalo, Southwest Papua, Central Papua, Mountainous Papua and South Papua) leaving only 30 provinces as data analysis units through purposive sampling. Data were analyzed using panel data regression analysis using Eviews-13. The results of the modeling selection determined that the selected model was a random effect model with a modeling contribution = 20.10%. The findings of this research provide evidence that higher inflation and foreign direct investment (FDI) have proven to have a real impact on economic growth, whereas a decrease in the exchange rate has proven unable to increase provincial economic growth in Indonesia.